Reinventing the Poet and Dark Lady: Theatricality and Artistic Control in Shakespeare's The Taming of the Shrew. (12th September 2013) - Tartamella, Suzanne M.
Abstract : Built on the premise that Shakespeare's poetic imagination inspired him to seek clarification and development beyond the boundaries of the Sonnets, this essay undertakes a cross‐genre study of The Taming of the Shrew and the dark‐lady sequence. Like the poems, The Taming of the Shrew examines the nature of artistic ownership and authority, and the power of theater to transform—even define—the self. But while the poet's creative experiments eventually spark the realization that he has developed a character too intractable for his own prescribed framework, Petruchio's rhetorical manipulations arguably begin with a fuller understanding of his authorial limits. That is, Petruchio knows that he must surrender control of his "dark lady" in return for a validation of his creative powers. Reading Petruchio's rhetorical strategies as an attempt to perfect the poet's negotiation tactics deployed on his mistress, the essay assumes a later date for The Taming of the Shrew and challenges prevailing views about the distinctions between Shakespeare's dramatic and lyric genres. Thus we can consider how sonnet 138—the cornerstone of Shakespeare's dark‐lady poems—underlies one of The Taming of the Shrew 's central tenets: that an author's intimacy with his creative work depends on his willingness to stand back and watch his work perform. (S. M. T.)